(untitled) (Heritage, 2023)
The choice of tradition, in the Eliot sense, determined two contemporary Serbian poets and brought their poetics closer to creating an alternative to cultural oblivion. It is a question of poetic turning to tradition (poetic memory) as a multi-layered alternative - a creative path of poetic memory in three directions: renewal of tradition, re-actualization of the topos of modesty and development of the song-prayer as a genre. The renewal of the dormant / neglected tradition, which implies a cultural vertical from Byzantine aesthetics, through the Serbian Middle Ages to the present day, is a poetic focus on a kind of nurturing, re-actualization of poetic heritage. The paper presents an analysis of the poems "Ten Addresses to the Mother of God Trojeručica Hilandarska" by Ljubomir Simović and "Bogorodica Trojeručica" by Matija Bećković from the aspect of poetic prayer defined by the modern Russian theory of literature, in the first place Valentina Avramova Maslova. Modesty as a general place of the medieval Serbian and Byzantine writing tradition is re-actualized in the mentioned poems in the function of framing the lyrical structure with elements of prayer and supplication. Motives that express modesty correspond to the motives of sinfulness of the individual and the collective, as well as to the motive of redemption, which is still in this form of contemporary Serbian poetry almost the same as in the Middle Ages. The rhetoric of self-humiliation results from the position of a lyrical subject who is homeless and crippled in Bećković’s poem, and in Simović’s conscious of the "stench of sins" of the collective to which he belongs. Repentance and desire, hope in mercy and forgiveness of sins, which is the basis of the medieval liturgical genre of prayer, are added to modesty. The work further illuminates the process of aesthetic permeation of the sacred and the secular (artistic), which is a key element of poetic prayer, which is an author’s lyrical poem based on the prayers and supplications of those from the new Middle Ages.